Bifidobacterium lactis Inhibits iNOS Expression in LPS-stimulated RAW 264.7 Macrophages - Bertoka Fajar Surya Perwira Negara; Jae Suk Choi (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Bifidobacterium is a genus of lactic acid bacteria that lives in the large intestine of humans and animals. The health benefits of this genus are well established; however, the anti-inflammatory activity of this genus, specifically Bifidobacterium lactis, has not been well defined. Therefore, in this study, we evaluated anti-inflammatory activity of B. lactis hydrolysates using lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages.METHODS: RAW 264.7 cells were cultured using Dulbecco’s Modified Eagle’s Medium in 5 % CO2 incubator at 37 ℃. One µg/mL of LPS was used to stimulate RAW 264.7 cells. Nitric oxide (NO) production, inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX-2) were measured to evaluate anti-inflammatory activity of B. lactis hydrolysates. The cytotoxicity of the inhibitor was also measured in present study through 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) assay.RESULTS: The results showed that B. lactis hydrolysates at 25–200 μg/mL inhibited NO production. In concentration-dependent manner, B. lactis hydrolysate showed inhibition of iNOS expression. However, no inhibition on COX-2 expression was observed. The MTS assay of the B. lactis hydrolysates showed no side effects on the cell viability at all concentrations.CONCLUSION: The current study revealed that B. lactis hydrolysates possess specific anti-inflammatory effects by inhibiting iNOS expression without cytotoxicity and therefore could potentially be developed as a new iNOS inhibitor.KEYWORDS: Bifidobacterium lactis, macrophages, hydrolysates, iNOS, COX-2